Mekanisme Bill of Lading Pengapalan Muatan Curah Cair Kapal Tanker Oleh PT. Equinox Sentra Bahari Cabang Belawan - Husniyah Husniyah; Syarifur Ridho; Dina Rispianti; Fadiyah Hani Sabila (Politeknik Kampar, 2023)
The purpose of writing this paper is to find out about the role of agents in the process of handling Bills of Lading for shipping liquid bulk cargo on tankers and the obstacles that occur in the process of handling Bills of Lading for shipping liquid bulk cargo on tankers by PT. Equinox Sentra Bahari Belawan Branch. The background underlying this paper is the Bill of Lading as an important document in the process of sending goods by sea transportation. The research used in writing this paper includes library research and field research which consists of interviews and observations carried out by the author based on the results of land practice at PT. Equinox Sentra Bahari Belawan Branch. Based on field observations, it was found that the agent's role in handling Bill of Lading documents by PT. Equinox Sentra Bahari Belawan Branch must be supported by other documents provided by the shipper and cargo carrier. PT. Equinox Sentra Bahari Belawan Branch will issue a Bill of Lading document after the ship departs or coincides with the ship's departure date and has been approved by the Shipper, Carrier and Consignee.